Enhancing Contextual Understanding and Critical Thinking in Fiqh Learning through Problem-Based Learning - Listrianti, Feriska; Hidayah, Tutik; Lama, Alma Vorfi (Journal of Islamic Education Research, 2025)
This study examines the impact of Problem-Based Learning (PBL) on students' participation, critical thinking skills, and understanding of fiqh concepts. Using a qualitative case study approach, data were collected through in-depth interviews, classroom observations, and document analysis. The findings indicate that PBL fosters a dynamic and inclusive learning environment, encouraging previously passive students to actively engage in discussions, share ideas, and connect fiqh theory to real-life contexts. Teachers observed increased student confidence in questioning, arguing, and problem-solving. These results highlight PBL as an effective alternative for enhancing fiqh education in madrassas and other Islamic institutions. By integrating PBL, students not only improve their conceptual understanding but also develop essential critical and collaborative thinking skills for their future.